Advances in ergonomics of manufacturing managing the enterprise of the future : proceedings of the AHFE 2017 International Conference on Human Aspects of Advanced Manufacturing, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA - Trzcielinski, Stefan (Advances in intelligent systems and computing, 2018)
This book discusses the latest advances in people-centered design, operation, and management of broadly defined advanced manufacturing systems and processes. It reports on human factors issues related to various research areas such as intelligent manufacturing technologies, web-based manufacturing services, digital manufacturing worlds, and manufacturing knowledge support systems, as well as other contemporary manufacturing environments. The book covers an extensive range of applications of human factors in the manufacturing industry: from work design, supply chains, evaluation of work systems, and social and organization design, to manufacturing systems, simulation and visualization, automation in manufacturing, and many others. Special emphasis is given to computer aided manufacturing technologies supporting enterprises, both in general and in the manufacturing industry in particular, such as knowledge-based systems, virtual reality, artificial intelligence methods, and many more. Based on the AHFE 2017 International Conference on Human Aspects of Advanced Manufacturing, held on July 17-21, 2017, in Los Angeles, California, USA, the book provides readers with a timely snapshot of the enterprises of the future and a set of cutting-edge technologies and methods for building innovative, human-centered, and computer-integrated manufacturing systems.